Solar fuel processing efficiency for ceria redox cycling using alternative oxygen partial pressure reduction methods. (August 2015) - Lin, Meng; Haussener, Sophia
Abstract: Solar-driven non-stoichiometric thermochemical redox cycling of ceria for the conversion of solar energy into fuels shows promise in achieving high solar-to-fuel efficiency. This efficiency is significantly affected by the operating conditions, e.g. redox temperatures, reduction and oxidation pressures, solar irradiation concentration, or heat recovery effectiveness. We present a thermodynamic analysis of five redox cycle designs to investigate the effects of working conditions on the fuel production. We focused on the influence of approaches to reduce the partial pressure of oxygen in the reduction step, namely by mechanical approaches (sweep gassing or vacuum pumping), chemical approaches (chemical scavenger), and combinations thereof. The results indicated that the sweep gas schemes work more efficient at non-isothermal than isothermal conditions, and efficient gas phase heat recovery and sweep gas recycling was important to ensure efficient fuel processing. The vacuum pump scheme achieved best efficiencies at isothermal conditions, and at non-isothermal conditions heat recovery was less essential. The use of oxygen scavengers combined with sweep gas and vacuum pump schemes further increased the system efficiency. The present work can be used to predict the performance of solar-driven non-stoichiometric redox cycles and further offers quantifiable guidelines for system design and operation. Highlights: A thermodynamic analysis was conducted for ceria-based thermochemical cycles. Five novel cycle designs and various operating conditions were proposed and investigated. Pressure reduction method affects optimal operating conditions for maximized efficiency. Chemical oxygen scavenger proves to be promising in further increasing efficiency. Formulation of quantifiable design guidelines for economical competitive solar fuel processing.